(untitled) (مجلة البحوث الأكاديمية, 2026)
Two novel random aromatic copolyesters (V and VI) containing dibenzylidenecyclohexanone units were synthesized via interfacial polycondensation and characterized by FTIR, EA, GPC, electrical conductivity measurements, and TGA. The copolyesters exhibited high molecular weights (Mn = 48,500–52,000 g mol⁻¹) and were insoluble in common organic solvents. Electrical measurements indicated insulating to semiconducting behavior with ohmic conduction. TGA results revealed excellent thermal stability, with decomposition temperatures above 369 °C and 50% weight loss occurring at 474 °C. The enhanced thermal resistance is attributed to the rigid aromatic and conjugated structures within the polymer backbone. These results demonstrate the potential of the synthesized copolyesters for high-performance and membrane-related applications